(3cJGH GdWgGQI ef TQM GdJdbjfs - (3CHhYHO Gddg eMeO Hf Ydj GdeGRQjs; (3YHO GdhgGH Hf Ydj GdHZOGOj GdeGdcj, CHh eMeO,J (B422 (3g` s
(3ChdgG (B:s
(3GdMeO ddg MeOkG jajO GdfYe Yf GdRhGd s
(3BNQgG (B:s
(3hJhdfG ajef JhdjJ hHGQc dfG ajeG CYWjJ hbfG s
(3Jdbjf GdeHJOj GfXQ cTa GdXfhf L (B1 (3U` (B481s
(3JHUQI GdYfhGf (B:s
(3TQMs
(3JHUQGJ GdCUd (B:s
(3GdfSNI eHJhQI GdBNQ s
(3GdfSNI HgG CQVg s
Keywords: (3Gdabg GdeGdcjs